Hubungan Tingkat Kecemasan dengan Tingkat Keparahan Insomnia pada Mahasiswa Semester 3 Fakultas Kedokteran dan Ilmu Kesehatan Universitas Warmadewa yang Akan Menghadapi Ujian OSCE pada Tahun 2021 - Anak Agung Mirah Gayatri; Made Dharmesti Wijaya; I Wayan Eka Arsana (Aesculapius Medical Journal, 2022)
Anxiety is a feeling of worry, nervous, and other unpleasant feelings. About one in three medical students worldwide experience anxiety. Anxiety experienced by students can make them suffer from insomnia. Insomnia is defined as a sleep disorder characterized by complaints of difficulty falling asleep, remaining asleep, and poor sleep quality. Objective Structured Clinical Examination (OSCE) is one of the exams that triggers anxiety in medical students. This study aims to determine the relationship between anxiety levels and the severity of insomnia among third semester students in the Faculty of Medicine and Health Sciences, Warmadewa University in facing the OSCE in 2021. A cross-sectional study with correlational quantitative approach was conducted on the respondents (n = 111). The respondents was selected using purposive sampling method. The data was collected using self-data questionnaire, as well as Hamilton Anxiety Rating Scale (HARS), and Insomnia Severity Index (ISI) questionnaires. The data obtained was analyzed using descriptive analysis, statistical analysis with Spearman Rank correlation analysis, and hypothesis testing with p-value on Sig (2-tailed) using SPSS software. The result shows that there is a positive correlation between the level of anxiety and the severity of insomnia with a moderate correlation strength (r=0.494) and statistically significant (p=0.001).